Initiation to the Principle - Nunes Sobrinho, Rubens Garcia (Revista Archai, 2011)
In the dialogue that dramatizes Socrates’ last philosophical discussion and words, Plato borrows a stock of images which were shaped on the Greek mystery cults’ mindsets in order to introduce the fundamental principles of his own Philosophy. His philosophic interlocutors, who represent a Pythagorean tradition, present the opportunity of a sophisticated argumentation that promotes an extreme inflection on the religious tradition and philosophical notions, which investigates the causal principles of all things. This study relies on the technical meaning of initiation, soulharmony and Socrates’ last words: an invitation of initiation to the principle.